A case for on-farm trials of fodder banks on the Adamawa Plateau in Cameroon - Tarawali, G.; Pamo, E.T. (Cambridge University Press, 1992)
The poor quality of the natural vegetation in the dry season affects both animal productivity and the lives of the pastoral community in the Adamawa Plateau of Cameroon but may be improved by introduction of the forage legume Stylosanthes guianensis. When used in a fodder bank system, Stylosanthes grew to an average plant height of 1.41m, had a dry matter productivity of 5.5 t ha and comprised 93.4 percent of the pastures botanical composition at the end of the growing season, indicating that fodder banks have considerable potential to enhance animal and crop production in Cameroon. Complementary studies conducted in Nigeria on the yield benefits of cropping leguminous pastures support the feasibility of using fodder banks as a means of improving the livelihoods of small scale farmers.